Errors in Otolaryngology Revisited. (May 2014) - Shah, Rahul K.; Boss, Emily F.; Brereton, Jean; Roberson, David W.
Objective: A decade ago, a survey study identified areas of risk and proposed a classification schema for otolaryngology errors. The objective of the present study is to obtain current data for comparison using a similar methodology. Study Design: Survey study. Setting: An anonymous online survey was distributed via the American Academy of Otolaryngology—Head and Neck Surgery (AAO-HNS) weekly email. Subjects and Methods: Members of the AAO-HNS were asked to describe any event in their practice that they felt should not have happened. Events were classified using the prior schema with minor modifications. Results: Of 681 respondents, 445 (66%) reported an event within the past 6 months, from which 222 reports were extracted. The mean age of the affected patients was 41 ± 24 years. An adverse consequence occurred in more than half of events, with corrective action taken in 82.8%. Of the respondents, 68% subsequently changed their practice patterns. The domains with the most reported errors were technical (27.9% of all events, 71% with major morbidity), administrative (12.2%, 3.7%), diagnostic testing (10.8%, 8.3%), and surgical planning (9.9%, 45.5%). There were 8 wrong-site surgeries, 23 cranial nerve injuries (91.3% major morbidity), and 9 errors during endoscopic sinus surgery (55.6% major morbidity). There were 4 deaths. Conclusion: There has been disappointingly little overall change. Otolaryngologists remain vulnerable to errors and related adverse events. The domains with the greatest risk for error-related major morbidity have changed little and include errors in technical, administrative, diagnostic testing, surgical planning, and surgical equipment. Awareness of high-risk areas may help to focus preventive efforts in these domains.